Mathematics Learning Application In The Form Of Android-Based Educational Games At Pancasila 4 Pracimantoro Junior High School - Puspitasari, Norma; Wahyudi, Muhammad Hari (International Journal of Computer and Information System (IJCIS), 2022)
Children in their in junior high school, still have many difficulties in learning, especially in calculating subjects such as mathematics. In class 7, 8, 9 a variety of variations of arithmetic operations one of which is arithmetic material. In addition to learning methods in the classroom, other methods such as practicing questions and also learning through games can be used. The method used in making mathematics learning applications in the form of this educational game is SDLC Waterfall. Starting from the analysis stage, flowchart design, storyboarding, asset programs, coding and making application logic to the testing stage, and finally the maintenance stage of the program in the form of an Android-based educational game that has been completed. Educational game about arithmetic material, starting from level 1 the player passes the enemy and picks up one book, after getting a book a question will appear, the player will get a value of 20 in each question asking for correct, if wrong then rating 0, if all books have been collected and all questions has been answered then the door at the end of the scene will open to proceed to the next level up to the last level which is 4. The results of manual tests and educational games also show an increase in student test scores, which can only be obtained with a value of 40, 6% to 53.2 %. It can be concluded that this educational game is feasible to be implemented in Pancasila 4 Pracimantoro Junior High School.